2018
DOI: 10.1080/14686996.2017.1422224
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of group IV graphene analogs

Abstract: Mono-elemental two-dimensional (2D) crystals (graphene, silicene, germanene, stanene, and so on), termed 2D-Xenes, have been brought to the forefront of scientific research. The stability and electronic properties of 2D-Xenes are main challenges in developing practical devices. Therefore, in this review, we focus on 2D free-standing group-IV graphene analogs (graphene quantum dots, silicane, and germanane) and the functionalization of these sheets with organic moieties, which could be handled under ambient con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 162 publications
0
24
0
Order By: Relevance
“… Carbonaceous materials of different dimensionalities. Reproduced from [ 24 ] with permission of Taylor & Francis. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Carbonaceous materials of different dimensionalities. Reproduced from [ 24 ] with permission of Taylor & Francis. …”
Section: Figurementioning
confidence: 99%
“…Graphene is a two-dimensional monolayer of sp 2 hybridized carbon atoms bonded covalently in a hexagonal lattice. It is a basic building block for carbon materials of all other dimensionalities, including 0D Bucky ball and graphene quantum dot (GQD), 1D carbon nanotube, and 3D graphite ( Figure 1 ) [ 24 ]. Graphene was firstly isolated from graphite by Geim and Novoselov through mechanical cleavage using a scotch-tape to attach flakes of graphene layers [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To data, computational researchers suggested that silicon atoms may form graphene‐like sheets, e.g., in silicene with sp 2 hybridized silicon ( Figure a) and in silicane with sp 3 hybridized silicon, forming a σ‐conjugated network (e.g., hydrogen‐terminated silicane shown in Figure b), unlike the conventional diamond structured silicon. On the other hand, many experimental scientists have attempted to synthesize these predicted 2D silicon materials, and various prototype applications have been demonstrated, including optoelectronic devices, catalysts, and energy storage devices …”
mentioning
confidence: 99%
“…121 Moreover, chemically modified 2D materials from group IVA and VA can have improved stability and tailored properties. 34,122 While top-down processes are time saving and costeffective, the bottom-up approach has the advantages in scalable preparation and composition control. It should be noted that improving the existing synthesis methods of 2D Xene to obtain materials with controllable size, morphology and composition is still a research hotspot of 2D materials.…”
Section: Synthesis Methodsmentioning
confidence: 99%